Nocturnal fabulations ecology, vitality and opacity in the cinema of Apichatpong Weerasethakul - Bordeleau, Érik; Pape, Toni; Rose-Antoinette, Ronald; Szymanski, André 1974- (Open Humanities Press, 2017)
Nocturnal Fabulations is an essay in intercessing. This is not a book that is simply ‘about’ Apichatpong Weerasethakul, though it does engage his work in detail. It is a book that deeply questions what else might be at stake in setting up the conditions for collaboration across two genres: cinema and writing. This collective project is animated by a shared curiosity in the pragmatics of fabulation and its speculative gesture of bringing forth a people to come. In an encounter with Apichatpong’s cinematic dreamscape, the concepts of ecology, vitality and opacity emerge to articulate an ethos of fabulation that deframes experience, recomposes ..
Keywords: Asian Cinema; cinema history; film studies; World Cinema; Aufsatzsammlung